Alternativni način preverjanja znanja - Lah, Anamarija (Vestnik za tuje jezike, 2011)
Testing and assessment is classified into two basic categories: formal and alternative. There are five basic types of tests in formal assessment. Alternative assessment on the other hand offers more possibilities of testing knowledge, but it has to satisfy the following criteria: 1. compatibility with the school curriculum, 2. feasibility, 3. child friendly (Pižorn 2010). Test-teach-test (TTT) method way of testing children's knowledge in German as an extracurricular activity in 6th grade of primary school was used as an alternative way of testing children's knowledge. This method showed not only the degree of their knowledge, but brought many results about factors that influence the acquisition.
Keywords: German; nemščina; TTT; tuji jeziki; test-teach-test; ocenjevanje znanja; preverjanje znanja; osnovne šole